The Impact of E-Service Quality and E-market Orientation on E-wom through E-trust as a Mediator for Shopee Users - kolefiyan, Ihsyan; Kurniawati, Hasni Dyah; Arofah, Ummu; Sari, Mirna Aulia; Saleh, Khoirul Alfian; Rabbani, Luthfi Dzaki (Jurnal Economic Resource, 2024)
This study aims to evaluate the impact of service quality (E-service quality) and E-Market Orientation (E-market orientation) on electronic word of mouth (E-WOM) through trust (E-trust) as an intermediary variable among Shopee users. This research uses a quantitative method that collects data through an online survey involving 107 respondents. Data analysis was carried out through Structural Equation Modeling (SEM) using SmartPLS 3.0. Research findings show that E-service quality and E-market orientation have a positive and significant influence on E-trust. Apart from that, E-trust has been proven to play a mediating role in the influence of E-service quality and E-market orientation on E-WOM. Validity and reliability tests show that the research instrument meets the required criteria, with a moderate R² value for the dependent variable. The findings from this research emphasize the importance of E-commerce companies such as Shopee to continue to improve service quality and E-Market Orientation in order to build consumer trust and encourage positive E-WOM